Evaluating the effect of students' behavioural intention to use social media for collaborative learning - Nur Shamsiah, Abdul Rahman; Noor Azida, Sahabudin (Elsevier, 2024)
With the rise of social media technologies, investigating the use of social media for learning has become all the more important. However, far too little research has been conducted to investigate factors that contribute towards students’ attitude and behavioural intention to use social media for collaborative learning in Malaysian higher education. This study aims to examine the determinants that influence students’ attitude and behaviour intention to use social media for collaborative learning by applying the Theory Acceptance Model (TAM) and Unified Theory of Acceptance and Usage of Technology (UTAUT). 243 respondents participated in this study. The Structural Equation modelling (SEM) was used to test the model fit and corresponding hypotheses. The findings indicated that students’ attitudes and behaviour are strong indicators of their intentions to use social media for collaborative learning.